Feasibility of Augmented Reality-Based Learning Media - Panjaitan*, Ruqiah Ganda Putri; Tenriawaru, Andi Besse; Pitiporntapin, Sasithep; Rifanka, Naura Irma; Fitriyani, Fitriyani; Hayati, Nurul (Jurnal Pendidikan Sains Indonesia, 2024)
One of the essential aspects of the learning process is instructional media. An instructional media that can be utilized is augmented reality (AR)-based instructional media. This research aims to assess the feasibility of AR-based instructional media on the digestive system. The stages involved in this research include gathering information through literature review, designing AR-based instructional media, validating AR-based instructional media, and revising AR-based instructional media based on validator feedback. The validation results of AR-based instructional media, with four assessment aspects including linguistic, illustration, attractiveness, and quality, obtained a score of 1.00, indicating a very high rating. AR-based instructional media can visualize digestive system material that cannot be directly observed through the presentation of illustrations such as images and videos that resemble real conditions, thereby reducing misconceptions about the digestive system material. It is concluded that AR-based instructional media is suitable for instructional media on the digestive system topic